Nuclear Gene Affecting Greening in Virescent Peanut Leaves - Benedict, C. R. (1972)
Chlorophyll synthesis induced by continuous illumination of dark-grown seedlings has been followed in wild-type and virescent peanut leaves. Compared to the wild-type leaves, chlorophyll synthesis in the virescent leaves shows a 72-hour lag period before the onset of a phase of rapid chlorophyll accumulation. The development of chloroplast grana and the activity of many enzymes of the reductive pentose phosphate cycle, phosphoenolpyruvate carboxylase, and malate dehydrogenase are reduced in the virescent leaves during the lag phase of chlorophyll accumulation. Although nucleic acid synthesis in the virescent leaves in normal, there is a distinctly lower rate of protein synthesis. The low level of protein synthesis during the lag period might limit the synthesis of a factor(s) essential for the development of both cell and chloroplast constituents.